Microfinance Models and Challenges in Sri Lanka. - Koperunthevy, K.; Vijayarani, K. (Annamalai University, India, 2012)
Microfinance uses by governments to improve living standard of poor households. Sri Lanka adopted several micro finance models such as Village Banking, Grameen type group collateral lending, Individual lending using group as a focal point, Individual lending, Self – Help Groups, Credit Union/ Cooperatives, and Rotation Saving and Credit Associations from 1911. Even though, the study identified that the government of Sri Lanka faces challenges regarding implementation of microfinance system. Lack of long-term vision and policy, lack of regulatory and supervisory framework, inadequate supervision of saving, politicization, insufficient specialized microfinance training facilities, limited knowledge transfer and information exchange within the sector, minimal specialized capacity among audit rating and information system fund, lack of credit information sharing, quality of human resources and corporate governance.